Identification of Microplastics in River Sediments: Type, Abundance, and Characteristics of Asam River Sediment, Jambi City - Riska Rahmah Dani Fitria; Nazarudin Nazarudin; Mohd Zuhdi; Yuni Haryati (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Microplastics have become a critical environmental pollutant in aquatic ecosystems, particularly in river sediments. The Asam River, a tributary of the Batanghari River in Jambi City, Indonesia, experiences substantial anthropogenic pressure from surrounding settlements, markets, and recreational areas. Objective: This study aimed to identify the types, abundance, colour variation, size distribution, and sediment characteristics of microplastics in the Asam River, Jambi City. Method: Sediment samples were collected from 9 sampling points using the grab sampling method (depth 0.8 – 1.2 m). Microplastic identification was performed by visual inspection under a stereo microscope. Sediment characterisation included analyses of water content, sand fraction, and silt content. Result and Discussion: A total of 152 microplastic particles were identified. Filaments dominated at 54.60%, followed by fibres (32.23%), fragments (10.52%), and granules (2.63%). Particle sizes ranged from 0.085 to 4.907 mm with a mean of 0.699 mm. Blue and transparent colours were predominant across all sampling points. Sampling point 1 recorded the highest abundance (30 particles; 20%), attributed to its proximity to dense urban activities and the Batanghari River confluence. Sampling point 6 had the lowest abundance (7 particles; 5%) and was located adjacent to plantation areas. Conclusion: Asam River sediment is contaminated by microplastics dominated by filament-type particles, with abundance strongly associated with proximity to human settlements and commercial activities.